Blood gas analyzer utility in evaluating oxygen kinetics of the aqueous humor - Ersan,Ismail (2015)
Purpose: To measure the partial pressure of oxygen (PO2) and carbon dioxide (PCO2) and the pH of aqueous humor (AH) and arterial blood samples from rabbits using a blood gas analyzer. Methods: Twenty New Zealand rabbits were anesthetized intramuscularly with ketamine and xylazine and were then allowed to breathe room air. Using a gas blood analyzer, arterial blood and AH samples were analyzed for PO2, PCO2, and pH. Results: The mean arterial blood pressure was 87.14 ± 15.0 mmHg. The mean blood and AH PO2 were 95.18 ± 11.76 mmHg and 88.83 ± 9.92 mmHg, the mean blood and AH PCO2 were 25.86 ± 5.46 mmHg and 29.50 ± 5.36 mmHg, and the mean blood and AH pH were 7.38 ± 0.06 and 7.33 ± 0.09, respectively. Conclusion: Conclusions: The blood gas analyzer was easily employed to evaluate the aqueous humor in rabbits. When comparing the results of studies evaluating aqueous PO2, care should be taken to determine the methods used in these studies.